Histological and Biometric Study of the Effects of Fusarium Graminarum Silver Nanoparticles on the Kidney in Male Albino Mice (Medico Legal Update, 2020)
An approach to synthesizing silver nanoparticles(AgNPs)using a Fusarium graminarum fungus wasestablished in the present study.These nanoparticles are identified with the following techniques to confirmthe form, size, and other physical properties of the crystal:UV-Visible Spectroscopy(UV-Vis),where theAgNPs showed absorbance at 420 nm, while X-Ray Diffraction (XRD)showed diffraction peaks at(38.05°,4nm).The experiment consisted of 40 mice divided into two groups, the first group of 20 mice was consideredto be the control animals and the other group 20mice was 21day of treatment with a dose of AgNPs(0.1ml/day).Microscopic examination of the kidney section showed lobulated glomeruli,a large area of hemorrhage,changes in degeneration, and inflammatory cell infiltration. Biometric changes of the renal corpuscle showedno significant difference between the study group,while Bowman’s capsule,Proximal,and distal convolutedtubules revealed increased significant differences between the two groups.